Insensitivity versus poor response to tumour necrosis factor inhibitors in rheumatoid arthritis: a retrospective cohort study - Sae Ochi; Kazuyoshi Saito; Fumitaka Mizoguchi; Shigeaki Kato; Yoshiya Tanaka (Arthritis Research & Therapy, 2020)
Abstract Background With advancement in the treatment options of rheumatoid arthritis (RA), optimising the outcomes of difficult-to-treat patients has become increasingly important in clinical practice. In particular, insensitivity to first-line biologic disease-modifying anti-rheumatic drugs (bDMARD) is becoming a significant problem because it may decrease the treatment adherence of patients. This study aimed to compare RA patients with an insensitivity and those with a poor response to initial treatment with tumour necrosis factor inhibitors (TNFis), which are the most frequently used bDMARDs. Methods This is a retrospective cohort study using clinical data from the FIRST registry. bDMARD-naïve RA patients treated with tumour necrosis factor inhibitors (TNFis) from August 2003 to May 2019 were included and categorised into three groups: TNFi insensitivity, poor response to TNFis and controls. TNFi insensitivity was defined as follows: (1) discontinuation of TNFi treatment within 22 weeks due to lack of any response, or (2) an increase in the disease activity score in 28 joints–C-reactive protein (DAS28-CRP) of > 0.6 at week 22 compared with week 0. Among the remaining patients, those with a DAS28-CRP > 2.6 at week 22 were categorised in the poor response group. Results Of the included patients, 94 were classified in the insensitivity, 604 in the poor response and 915 in the control. A higher DAS28-CRP before treatment was a risk factor for a poor response but not for insensitivity. In contrast, dose escalation of infliximab decreased the risk of a poor response but not that of insensitivity. Conclusions In future research, poor and insensitivity to bDMARDs should be assessed separately to fully elucidate the aetiology of, and risk factors for, bDMARD refractoriness.